Quran Memorization As A Vital Identification Process Of Gifted And Talented Muslim Students - Zulkarnin Zakaria; Mohd Zamrus Mohd Ali; Wan Ahmad Zakry Wan Kamaruddin; Abdel Rahman Ibrahim Suleiman Islieh; Rossidi Usop; Mahiz Spawi; Ahmad Fuad Mohamad Amin; Musa Mohamad (Universiti Sains Islam Malaysia, 2024)
PAPER PROCEEDINGS THE 7TH INTERNATIONAL CONFERENCE ON QURAN AS FOUNDATION OF CIVILIZATION (SWAT) 2021 “ISLAMIC AND NON-REVEALED KNOWLEDGE IN FACING THE GLOBAL CHALLENGES” 6th – 7th October 2021 / 29 – 30 Safar 1443H Faculty of Quranic and Sunnah Studies Universiti Sains Islam Malaysia